2015
DOI: 10.1007/s40617-015-0067-y
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Complex Verbal Operants with the PEAK Relational Training System

Abstract: The present study evaluated the effectiveness of five packaged protocols from the Promoting the Emergence of Advanced Knowledge (PEAK) curriculum. The skills targeted in the study included complex verbal operants proposed by Skinner (Verbal behavior. Englewood Cliffs, NJ: Prentice Hall, 1957), an area that is lacking in the current literature. The target skills included autoclitics, metonymical tacts, tacting planet names, and guessing. The results suggest that the PEAK methodology was effective in teaching ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 6 publications
0
12
0
6
Order By: Relevance
“…First, high ICCs were found—the literature regularly notes that ICCs above .800 indicate near perfect relations—even though potential limitations to the normative data (see below) and the component analysis (see below) are identified here. The ICCs might lend credibility to the construct validity and normative references, except that in McKeel, Rowsey, Belisle, Dixon, and Szekely (), a second administration of the PEAK‐DTA at 30 days—similar to Dixon et al ()—produced mixed results with some participants improving without intervention and others degenerating their score even with PEAK‐DTM intervention. A more thorough review of McKeel, Rowsey, Belisle et al is provided below.…”
Section: Conclusion Regarding Peak‐dtm and Peak‐dtamentioning
confidence: 86%
See 1 more Smart Citation
“…First, high ICCs were found—the literature regularly notes that ICCs above .800 indicate near perfect relations—even though potential limitations to the normative data (see below) and the component analysis (see below) are identified here. The ICCs might lend credibility to the construct validity and normative references, except that in McKeel, Rowsey, Belisle, Dixon, and Szekely (), a second administration of the PEAK‐DTA at 30 days—similar to Dixon et al ()—produced mixed results with some participants improving without intervention and others degenerating their score even with PEAK‐DTM intervention. A more thorough review of McKeel, Rowsey, Belisle et al is provided below.…”
Section: Conclusion Regarding Peak‐dtm and Peak‐dtamentioning
confidence: 86%
“…Finally, while McKeel, Rowsey, Belisle et al () marketed itself as an effectiveness study (as did Dixon et al, ), consider that the goal of the study was to work toward external validity for applied settings (p. 244). As the methods did not report if the authors, research assistants, or those with little experience implementing interventions administered the program, a conservative designation rests with efficacy rather than effectiveness.…”
Section: Conclusion Regarding Peak‐dtm and Peak‐dtamentioning
confidence: 99%
“…A final limitation was the homogeneity of the participants in the investigation. Participants were between 19 and 21 years of age, were male, and had low PEAK‐DA pretest scores relative to prior investigations on PEAK‐DT (e.g., Dixon et al, ; McKeel, Rowsey, Belisle, et al, ). It remains to be seen if the results would be replicated with participants who have higher preinstructional language and communication skills or are older than those in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Through PEAK-DT, learners progress through increasingly complex verbal operant skills guided by the PEAK-DTA. Prior research has supported the effectiveness of the procedures described in PEAK-DT in teaching target skills in single-case evaluations (Dixon, Belisle, Munoz, Stanley, & Rowsey, 2017;McKeel, Rowsey, Belisle, et al, 2015) as well as in a randomized controlled evaluation . Results reported by McKeel, Rowsey, Belisle, et al (2015) showed that the procedures described in PEAK-DT were efficacious in teaching two children with autism to correctly demonstrate basic autoclitics, receptive metonymical tacting, and expressive identification of planet names, and one child with autism receptive metonymical tacting, expressive metonymical tacting, and guessing.…”
mentioning
confidence: 99%
“…Peer-Reviewed Support for PEAK There are several peerreviewed, published articles examining the effectiveness and psychometric properties of PEAK-DT, PEAK-G, PEAK-E, and PEAK-T (e.g., Belisle, Dixon, Stanley, Munoz, & Daar, 2016;Dixon, Belisle, Whiting, & Rowsey, 2014a;Dixon et al, 2014b;Dixon, Whiting, Rowsey, & Belisle, 2014c;McKeel, Dixon, Daar, Rowsey, & Szekely, 2015a;McKeel, Rowsey, Belisle, Dixon, & Szekely, 2015b;McKeel, Rowsey, Dixon, & Daar, 2014;Rowsey, Belisle, & Dixon, 2014). PEAK has demonstrated reliability (e.g., PEAK-DT: Dixon, Stanley, Belisle, & Rowsey, 2016), internal validity (e.g., PEAK-DT: Rowsey et al, 2014;PEAK-G: Dixon et al, 2017b), and external validity (PEAK-DT: Dixon et al, 2014b;Dixon et al, 2014b;Malkin, Dixon, Speelman, & Luke, 2017;McKeel et al, 2014;PEAK-G: Dixon et al, 2015;Dunkel-Jackson, 2016).…”
Section: Peakmentioning
confidence: 99%